(untitled) (Innovative professional education, 2024)
During martial law, the values and competencies that students acquire during their college studies remain extremely important. Teachers’ efforts to form spiritual and moral values in young people, to provide them with orientations with which they can go through life, become a priority. Notice and timely prevent the development of pseudo-values that are formed in a short period of time and significantly worsen the behavior of students. It is necessary to constantly carry out educational work and encourage students to socialize and create conditions for the spiritual growth of young people.